Development of Competency in Active Learning Management of Teachers That Affects Student Quality at Banpamaisahakorn School Buriram Primary Educational Service Area Office 3: Development of Competency in Active Learning Management of Teachers That Affects Student Quality at Banpamaisahakorn School Buriram Primary Educational Service Area Office 3 - Thungthaisong , Pawinee (RATANABUTH JOURNAL, 2024)
The research aims to 1) Develop the competency in active learning management of teachers at Ban Pa Pa Mai Sahakorn School.2) Study the results of using the model for developing competency in active learning management of teachers at Ban Pa Pa Sakorn School.The sample group consisted of 27 teachers who received the development and students, which were obtained using a simple random sampling method.The tools used in the research are Structured interviews, assessments, tests, and questionnaires.Basic statistics include frequency, percentage, mean, and standard deviation. Statistics used for comparison were One Sample t-test and Two Sample t-test, t-test for Dependent, and qualitative data were analyzed using content analysis. The results of the research found that: 1) The development of teachers’ competency in active learning management was found to be1.1) Creating guidelines for developing teachers’ competency in active learning management. Consists of 6 steps of operations:Step 1 Setting goals Step 2 Development planning Step 3 Development operations It consists of five steps of active learning management: 3.1) building inspiration, 3.2) learning from practice, 3.3) reflection, 3.4) discussion and conclusion, and 3.5) application of knowledge and evaluation. Step 4: Monitoring and evaluating, Step 5: Reflecting on results, and Step 6: Dissemination to all involved parties.1.2) The model for developing competency in active learning management is appropriate at a high level. and each component of the learning management competency development process is consistent with one another.2) The results of using the model for developing teachers’ active learning competencies that affect student quality were found.2.1) The competency in active learning management of the teachers who received the development was at a very good level. 2.2) Grade 4 students had a higher average academic achievement score after learning than before learning. Statistically significant at the .05 level. 2.3) Grade 4 students had a higher mean score in analytical thinking ability after studying than before, with statistical significance at the .05 level.2.4) Students are satisfied with the active learning management by the teachers who received the development at a high level. The average satisfaction level is different from the average value that is the criterion value. Statistically significant at the level of .05 and higher than the criterion average. 2.5) Teachers who received the development were satisfied with the model for developing teachers’ active learning competencies that affected the quality of learners. At the highest level 2.6) Participants were satisfied with the exhibition of student work. at the highest level